Data Curation atU.Porto: Identifying current practices across disciplinary domains - Cristina Ribeiro (2011)
The University of Porto is the largest Portuguese university with more than 60 research centers that generate a significant part of Portuguese scientific production. U.Porto is currently concerned with the curation of and the access to the scientific data generated by its researchers. Researchers are motivated to keep their data assets alive as integral part of their published results, and the scientific impact derived from open datasets is also becoming apparent. We have followed the recommendations from well-known actions in research dataset auditing to lead a short study on available data at U.Porto. The study has involved researchers from a diversity of disciplines, collecting their views on data curation and sample data. As a result we have identified some generic use cases to inform the development of a data repository prototype. Our contacts with the researchers have revealed a great diversity of situations, from groups where data curation was already integrated in the research practice to others who were struggling to incorporate it into their workflows. Our experiment was focused on data auditing and use case identification, but we also concluded that in many groups there is a strong concern with the premature exposure of the data. The sample datasets provided by the researchers are being transformed into preservationfriendly archives to be part of a data repository. We will extend the repository infrastructure with data search facilities and expect feedback from the researchers to help define the research data management services at U.Porto.